Comparative Analysis of the Tragic Characters of Jay Gatsby and Jia Baoyu - Wang, Qian; Huang, Chi (International Journal of Social Sciences and Public Administration, 2024)
Jay Gatsby in The Great Gatsby and Jia Baoyu in A Dream of Red Mansions are two famous tragic characters in American and Chinese literary works respectively. By comparing the two figures, this paper probes into the similarities and differences of their personalities and the social reality they reflect. This paper first analyzes the background, character and status of Gatsby and Jia Baoyu respectively, and then compares their similarities and differences, discussing how these similarities and differences reflect their respective social backgrounds. Finally, the article turns to the inspiration of these two tragic figures on the contemporary society.